1972
DOI: 10.1002/pol.1972.160100302
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric behavior of aqueous solutions of sodium carboxymethyl cellulose

Abstract: Measurements are reported for the dielectric loss factor of the SCMC solutions over the frequency range 2 MHz to 50 MHz as a function of concentration of SCMC, concentration of added sodium chloride, molecular weight, and temperature. The results are in general agreement with those of other workers and are interpreted in terms of ionic theories in which motion of the diffuse counterions is the dominant feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Allen et al [13] proposed motion of counterions in the ionic atmosphere around polyelectrolyte molecule as the origin of the HF relaxation, but this mechanism seems to be difficult to explain the negative value of Aa E.…”
Section: Relaxation Amentioning
confidence: 97%
See 2 more Smart Citations
“…Allen et al [13] proposed motion of counterions in the ionic atmosphere around polyelectrolyte molecule as the origin of the HF relaxation, but this mechanism seems to be difficult to explain the negative value of Aa E.…”
Section: Relaxation Amentioning
confidence: 97%
“…Allg6n and Roswall [11,12] and later Allen et al [13] observed a dielectric relaxation of aqueous CMC at 0.3 to 20 MHz. Their results suggest that our constant part of An at 100 kHz may relax with further increase of frequency above 100 kHz, which is denoted relaxation A in the following.…”
Section: General Behaviormentioning
confidence: 98%
See 1 more Smart Citation